Lesson Objectives

- Demonstrate an understanding of exponents and logarithms
- Learn how to solve exponential equations with different bases

## How to Solve Exponential Equations with Logarithms

Before we jump in and start solving exponential equations, let's look at some of the properties we will be using in this lesson.

Example 1: Solve each equation $$6^x=15$$ To solve this equation, we can take the log of each side. $$log(6^x)=log(15)$$ Using our power rule for logarithms, we can bring the exponent (x) down in front of the logarithm on the left side of the equation. $$xlog(6)=log(15)$$ To get x by itself, we divide each side of the equation by log(6). $$x=\frac{log(15)}{log(6)}$$ This is our answer. If the teacher or assignment calls for a decimal approximation, we can divide using a calculator and then round to the appropriate number of decimal places.

One thing to note, the textbook may give you an alternative method for solving this type of equation. Notice that our base of the exponential expression is a 6. Recall the property of logarithms that tells us:

log

Therefore, we can also solve the equation in the following way: $$6^x=15$$ $$log_{6}(6^x)=log_{6}(15)$$ $$x=log_{6}(15)$$ Since using the change of base rule gives us our answer above, we can see that both answers are the same. It is just a matter of personal preference.

Example 2: Solve each equation $$10 \cdot 19^{4 - x}- 5=77$$ To solve this equation, we want to isolate the exponential expression. This will allow us to use logarithms and bring the variable down out of the exponent. We will begin by adding 5 to each side: $$10 \cdot 19^{4 - x}=82$$ Now we will divide each side by 10: $$19^{4 - x}=\frac{82}{10}$$ We can reduce our fraction on the right: $$19^{4 - x}=\frac{41}{5}$$ Now, we can take the log of each side: $$log(19^{4 - x})=log\left(\frac{41}{5}\right)$$ Bring the exponent (4 - x) out in front: $$(4 - x)log(19)=log\left(\frac{41}{5}\right)$$ Divide each side by log(19): $$4 - x=\frac{log\left(\frac{41}{5}\right)}{log(19)}$$ Subtract 4 away from each side: $$-x=\frac{log\left(\frac{41}{5}\right)}{log(19)}- 4$$ Multiply each side by -1: $$x=-\frac{log\left(\frac{41}{5}\right)}{log(19)}+ 4$$ Example 3: Solve each equation $$e^{x - 3}- 4=10$$ Let's begin by isolating our exponential expression. We will add 4 to each side of the equation: $$e^{x - 3}=14$$ When e is involved, we want to use ln.

Remember ln is log

### Properties for Solving Exponential and Logarithmic Equations

- b, x, and y are real numbers, b > 0, b ≠ 1
- If x = y, then b
^{x}= b^{y} - If b
^{x}= b^{y}, then x = y - If x = y and x > 0, y > 0, then log
_{b}(x) = log_{b}(y) - If x > 0, y > 0 and log
_{b}(x) = log_{b}(y), then x = y

### Solving Exponential Equations with Different Bases

Previously, we learned how to solve exponential equations with the same base. For that scenario, we can set the exponents equal to each other and solve for the unknown. We can't do this with every scenario since it is not always possible to have the same base on each side of an equation. When we try to solve an exponential equation and different bases are involved, we use logarithms to obtain our solution. We will first isolate the exponential expression and then we can take logarithms to the same base on both sides. This will allow us to use our product rule for logarithms to isolate the variable. Let's look at a few examples.Example 1: Solve each equation $$6^x=15$$ To solve this equation, we can take the log of each side. $$log(6^x)=log(15)$$ Using our power rule for logarithms, we can bring the exponent (x) down in front of the logarithm on the left side of the equation. $$xlog(6)=log(15)$$ To get x by itself, we divide each side of the equation by log(6). $$x=\frac{log(15)}{log(6)}$$ This is our answer. If the teacher or assignment calls for a decimal approximation, we can divide using a calculator and then round to the appropriate number of decimal places.

One thing to note, the textbook may give you an alternative method for solving this type of equation. Notice that our base of the exponential expression is a 6. Recall the property of logarithms that tells us:

log

_{b}(b^{x}) = xTherefore, we can also solve the equation in the following way: $$6^x=15$$ $$log_{6}(6^x)=log_{6}(15)$$ $$x=log_{6}(15)$$ Since using the change of base rule gives us our answer above, we can see that both answers are the same. It is just a matter of personal preference.

Example 2: Solve each equation $$10 \cdot 19^{4 - x}- 5=77$$ To solve this equation, we want to isolate the exponential expression. This will allow us to use logarithms and bring the variable down out of the exponent. We will begin by adding 5 to each side: $$10 \cdot 19^{4 - x}=82$$ Now we will divide each side by 10: $$19^{4 - x}=\frac{82}{10}$$ We can reduce our fraction on the right: $$19^{4 - x}=\frac{41}{5}$$ Now, we can take the log of each side: $$log(19^{4 - x})=log\left(\frac{41}{5}\right)$$ Bring the exponent (4 - x) out in front: $$(4 - x)log(19)=log\left(\frac{41}{5}\right)$$ Divide each side by log(19): $$4 - x=\frac{log\left(\frac{41}{5}\right)}{log(19)}$$ Subtract 4 away from each side: $$-x=\frac{log\left(\frac{41}{5}\right)}{log(19)}- 4$$ Multiply each side by -1: $$x=-\frac{log\left(\frac{41}{5}\right)}{log(19)}+ 4$$ Example 3: Solve each equation $$e^{x - 3}- 4=10$$ Let's begin by isolating our exponential expression. We will add 4 to each side of the equation: $$e^{x - 3}=14$$ When e is involved, we want to use ln.

Remember ln is log

_{e}$$ln(e^{x - 3})=ln(14)$$ $$x - 3=ln(14)$$ We will add 3 to each side of the equation: $$x=ln(14) + 3$$#### Skills Check:

Example #1

Solve each equation. $$4 \cdot 12^{5x + 2}=23$$

Please choose the best answer.

A

No Solution

B

$$x=\frac{log_{2}\left(\frac{11}{4}\right)}{5}$$

C

$$x=\frac{log_{12}\left(\frac{23}{4}\right) - 2}{5}$$

D

$$x=\frac{log_{23}(21) - 4}{5}$$

E

$$x=\frac{log_{14}(61) + 9}{9}$$

Example #2

Solve each equation. $$5 \cdot 11^{3x + 10}=11$$

Please choose the best answer.

A

$$x=\frac{log_{5}(20)}{3}$$

B

$$x=\frac{log_{11}\left(\frac{11}{5}\right) - 10}{3}$$

C

$$x=\frac{log_{5}\left(\frac{10}{11}\right) - 11}{3}$$

D

$$x=\frac{log_{11}(5) - 3}{11}$$

E

No Solution

Example #3

Solve each equation. $$14^{9x - 9}+ 3=64$$

Please choose the best answer.

A

No Solution

B

$$x=\frac{15}{7}$$

C

$$x=\frac{log_{14}\left(61\right) + 9}{9}$$

D

$$x=\frac{log_{14}\left(\frac{13}{64}\right) - 3}{9}$$

E

$$x=\frac{-log_{14}\left(\frac{55}{14}\right) + 3}{9}$$

Congrats, Your Score is 100%

Better Luck Next Time, Your Score is %

Try again?

Ready for more?

Watch the Step by Step Video Lesson Take the Practice Test